From Kitab Kuning to Digital Content: The Political Theology of BIWALI Pesantren in the 2024 Regional Elections - Ahmad, Ikhsan; Haq, Mochamad Ziaul (Parahyangan Catholic University, 2025)
This study aims to analyze how the traditional pesantren kobong Bintang Sembilan Wali (BIWALI) in Banten reconstructs Islamic political theology through digital media during the 2024 Simultaneous Regional Elections. The research addresses the urgency of understanding how religious institutions adapt to algorithmic political communication and navigate the blurred boundaries between dakwah and electoral propaganda. Employing a qualitative case study approach, the study combines online observation of BIWALI’s official social media accounts with literature analysis to examine the epistemological, sociological, and practical dimensions of digital dakwah content. The findings reveal three major insights: first, BIWALI transforms the authority of the kitab kuning into algorithmically shaped visual narratives; second, it uses moral dakwah as a strategic medium for political endorsement; and third, it triggers public polarization that challenges the singular authority of pesantren in digital discourse. These results suggest that pesantren have evolved into active political actors capable of shaping public opinion in the digital sphere. The research contributes to the fields of Islamic communication, digital religion, and political theology by showing how pesantren function as producers—not merely preservers—of Islamic discourse. Its originality lies in exploring pesantren kobong as algorithmic agents that reinterpret religious authority and communication ethics in the age of viral politics, offering a fresh theoretical and empirical perspective to the study of Islamic institutions in contemporary democracy.